2020
DOI: 10.3390/rs12152383
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential Use of RADARSAT-2 and UAS imagery for Monitoring the Restoration of Peatlands

Abstract: The restoration of peatlands is critical to help reduce the effects of climate change and further prevent the loss of habitat for many species of flora and fauna. The objective of this research was to evaluate RADARSAT-2 satellite imagery and high-resolution Unmanned Aerial Systems (UASs) to determine if they could be used as surrogates for monitoring the success of peatland restoration. Areas of peatland that were being actively harvested, had been restored from past years (1994–2003), and natural shrub bog i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…UAV-based restoration monitoring involves a variety of objectives, including biomass estimates [120], hydrological mapping [8,9,11,123], morphological evaluations [43,57], and classification of plant communities in peatlands [10,56,119,122] and coastal regions [44,117,118,121]. While many researchers leverage RGB aerial imagery for restoration monitoring [8,9,120,122,123], multispectral imagery, and specifically the near-infrared wavelength, which can detect species and topography in shallow wetland environments [155].…”
Section: Restoration and Management Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…UAV-based restoration monitoring involves a variety of objectives, including biomass estimates [120], hydrological mapping [8,9,11,123], morphological evaluations [43,57], and classification of plant communities in peatlands [10,56,119,122] and coastal regions [44,117,118,121]. While many researchers leverage RGB aerial imagery for restoration monitoring [8,9,120,122,123], multispectral imagery, and specifically the near-infrared wavelength, which can detect species and topography in shallow wetland environments [155].…”
Section: Restoration and Management Outcomesmentioning
confidence: 99%
“…Only 55 studies (~46% of the pool) reported some form of survey and image mosaicking error. Since implications of mosaicking and positioning errors are likely to substantially vary among management goals (e.g., [28,119,128,133]), the lack of clear accuracy benchmarks as well as standards for accuracy and error reporting in UAV applications presents an important action item for the wetland UAV community in the future.…”
Section: Field Operations In Wetland Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several UAS methods have also been applied in peatland restoration monitoring. Many methods [28][29][30][31][32] are restricted to two-dimensional products, such as orthomosaic pictures for the classification of vegetation coverage. However, there are also examples of UAS-SfM-based topographical analysis [21,33,34].…”
Section: Introductionmentioning
confidence: 99%